1991
DOI: 10.1523/jneurosci.11-01-00226.1991
|View full text |Cite
|
Sign up to set email alerts
|

Chemically distinct compartments of the thalamic VPM nucleus in monkeys relay principal and spinal trigeminal pathways to different layers of the somatosensory cortex

Abstract: The ventral posteromedial nucleus (VPM) of the monkey thalamus was investigated with combined immunocytochemical, histochemical, and connection-tracing techniques. Injections of anterogradely transported tracers were placed selectively in the caudal nucleus of the spinal trigeminal nuclear complex, and retrogradely transported horseradish peroxidase (HRP) or fluorescent dyes were placed on the surface or into the depths of defined parts of the trigeminal representation in the first somatic sensory area (SI) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
102
0
2

Year Published

1993
1993
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(112 citation statements)
references
References 30 publications
8
102
0
2
Order By: Relevance
“…1). Enclosed within the lamina are the larger Nissl-stained cells that form the rod domain of the nucleus (Rausell and Jones, 1991a) and smaller cells of the matrix domain of VPM that include the small-celled zone of VPM and the basal ventral medial nucleus (VMb). The aggregated cells of the rods stain intensely for CO and for parvalbumin, and the rods at the medial tip of VPM also costain for calbindin, forming the densest focus of calbindin immunoreactivity in the posterior thalamus (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Enclosed within the lamina are the larger Nissl-stained cells that form the rod domain of the nucleus (Rausell and Jones, 1991a) and smaller cells of the matrix domain of VPM that include the small-celled zone of VPM and the basal ventral medial nucleus (VMb). The aggregated cells of the rods stain intensely for CO and for parvalbumin, and the rods at the medial tip of VPM also costain for calbindin, forming the densest focus of calbindin immunoreactivity in the posterior thalamus (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…It seems likely that the injections described by Craig et al (1994) were too small and of too limited a rostrocaudal extent to reveal the complex and widespread pattern of projections from lamina I to the thalamus (Jones, 2002;Willis et al, 2002;Ralston, 2003); however, the account of labeled terminations of STT and sVTT axons representing the face, body, and limbs being found exclusively in the calbindin-rich tip of VPM cannot be correct. From mapping studies, the medial tip represents only ipsilateral intraoral structures (Rausell and Jones, 1991a) and projects to primary somatosensory cortex (Manger et al, 1995(Manger et al, , 1996, not to the cingulate region.…”
Section: Lamina I Projections To the Thalamus: The Connectivity Issuementioning
confidence: 99%
“…Because most cortically projecting neurons were found to be PAG ϩ , we concluded that the Calb ϩ cortically projecting neurons most probably contain this enzyme and are thus potentially glutamatergic. Such cells may parallel in their projections and actions the Calb ϩ glutamatergic neurons of the thalamus (Frassoni et al, 1997), which provide a widespread projection to the superficial layers of the cerebral cortex (Rausell and Jones, 1991;Jones, 1998). The vast majority of Calret ϩ neurons was immunopositive for PAG and not retrogradely labeled from the cortex, thus likely corresponding to glutamatergic neurons with caudally or locally directed projections.…”
Section: Colocalization Of Cbp With Chat Gad or Pag In The Bfmentioning
confidence: 99%
“…Thus, the small cells in VP are not targets of the lemniscal path (11,12), and the small cell layers of GL in galago (layers 4 and 5) receive small fibers from the superior colliculus (SC), which, in turn, is the target of the smallest fibers of the optic tract (3,13). The general principle we seek may simply be that pathways to the superficial layers Abbreviations: GL, lateral geniculate nucleus; Lat, lateral nuclear group; Po, posterior nuclear group; Pul, pulvinar nucleus; SC, superior colliculus; VP, ventral posterior nucleus; VPi, inferior division of the VP; VPs, superior division of the VP.…”
mentioning
confidence: 99%
“…In the past few years, Jones and his colleagues (11,12,14) have shown that large and small cells in the thalamus differ in their staining for calcium binding proteins, calbindin and parvalbumin. The clusters of big cells in VP of the monkey are rich in parvalbumin, whereas the small, pale cells in the matrix are rich in calbindin.…”
mentioning
confidence: 99%